GALILEO open learning materials [electronic resource] (GALILEO Affordable Learning Georgia, 2020)
Quoted from the homepage: GALILEO Open Learning Materials is our current USG-wide repository for all created resources under Affordable Learning Georgia, including resources created under Affordable Materials Grants (previously Textbook Transformation Grants), our open textbooks created in partnership with the University of North Georgia Press, and all other ALG programs. Documents in GALILEO Open Learning Materials is classified by its Creative Commons license. These licenses allow you to reuse, redistribute, revise, remix, and retain these documents, with particular restrictions per the license. To learn more about the types of licenses, check out the Creative Commons License Page.